Bahasa Ruang Publik Lembaga Pemerintah di Kepulauan Riau - Tasliati - (Jurnal Archipelago, 2024)
Writings in public spaces not only function as a tool for information but also as a means to represent the linguistic attitude of their creators. If created and published by government institutions, the linguistic attitude of the institution will be reflected. In essence, government institutions can serve as examples in the application of language rules in public spaces, especially in the Riau Islands, which has a strong historical connection to the birth of the Indonesian language. Therefore, this study aims to describe the language used in the public spaces of government institutions in the Riau Islands. Data were collected using the "simak" method, with observation and documentation techniques. The data were then analyzed using the distributional method and the matching method. The research findings show that in public spaces of government institutions in the Riau Islands, numerous indications of non-compliance with language regulations were observed, including the use of foreign languages and deviations from linguistic norms. Among these, deviations from linguistic norms are more dominant as they encompass various aspects, namely spelling, word choice, and structure. These indications of non-compliance were found across all categories of public spaces monitored, including the writings of institution or building names, public facility names, meeting room names, product or service names, job titles, directional signs or general markers, and writings in the form of banners or similar types of information.